Training for improving employee work ethics after the Covid-19 pandemic at the Faculty of Dentistry, University of North Sumatra - Ahmad Afandi; Fajar Hasan Mursyid (Community Empowerment, 2022)
The Covid-19 pandemic has shifted the work process to Work From Home (WFH), resulting in lower staff performance, particularly at the Faculty of Dentistry, University of North Sumatra (FKG USU). Work activities resumed in the office at the beginning of 2022, although productivity remained low. As a result, initiatives to encourage employee performance development, such as through training to increase employee work ethic, are required. Identification of partner issues, training, and evaluation are the three stages of this program. Participants were satisfied with the substance and design of the training delivered, according to the evaluation results. This program has a great influence since it teaches employees how to enhance their work ethic and make work activities meaningful as worship.